Kesesakan sebagai Prediktor Kesejahteraan Psikologis: Studi di Kampung Biru Arema Kota Malang - Agung Minto Wahyu; Luky Karisma; Qoni’atur Ridwan; Anita Hariyanti; Mochammad Sa’id (Journal An-Nafs: Kajian Penelitian Psikologi, 2020)
Every human who lives in the world has aspirations for prosperity in his life. This well-being is not only materially, but also psychological well-being. However, the increasing density of the physical environment will potentially lead to the perception of crowding and have an impact on the psychological well-being of individuals. This study aims to investigate the effect of distress on psychological well-being in the community in Kampung Biru Arema Malang. This study uses a quantitative correlational design with regression analysis to determine the effect of the crowding variable on the psychological well-being variable. Respondents selected as samples in this study were 38 people who were residents of Kampung Biru Arema. The samples were conducted research using non-probability sampling technique is purposive sampling. Data collected by using two scales, the scale of distress and the psychological well-being scale. The results of this study indicate that adversity has a significant negative influence as a predictor of psychological well-being in communities in Kampung Biru Arema Malang (t hitung= -3,213; p<0.05; R Square = 0,223). This study concludes that individuals who perceive the density as crowding will decrease their psychological well-being.